Peningkatan Nilai Nutrisi Cangkang Siput Sebagai Sumber Mineral Pada Ransum Ayam Buras Periode Grower - Khalil Khalil (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The objectives of the present investigation were to evaluate the effect of using shell of fresh water snails in 3 different processing forms (raw coarse ground, raw and roasted finely ground) as the major source of calcium in the diets on the performance of growing native chickens (12-24 weeks of age). Four dietary treatments were a control diet containing 2 % of oyster shell meal and three others consisted of 2 % of freshwater snail shell in the form raw coarse ground, raw and roasted fine ground. The diets were offered to forty growing native chicks, which were randomly divided into four groups, each amounting of 10 chickens as replication. Parameters measured included: body weight gain, feed intake, FCR, carcass weight and net return. The results showed that roasting of shell of freshwater snail prior to incorporate in the rations could significantly improve the body weigh gain, feed intake and FCR However, the net return was negative mainly due to high feed cost. Chickens fed on diet containing raw coarse grounded shell was found the highest net return.